Application Characteristics of Ammonium Dinitramide to HTPB Composite Propellants - Xu, Hui-Xiang; Zhao, Feng-Qi; Pang, Wei-Qiang; Guo, Hong-Wei; Sun, Zhi-Hua; Fan, Xue-Zhong (Asian Journal of Chemistry, 2014)
In order to reduce signal and increase energy of HTPB composite propellants, ammonium dinitramide (ADN) was applied to this formulation. Using SEM, vacuum stability test (VST) and other standard methods, mechanical sensitivity, thermal stability and combustion properties of HTPB/ADN propellant were tested. Results show that the mechanical sensitivity of HTPB/ADN propellants increase for higher friction sensitivity and impact sensitivity of ammonium dinitramide, while effect of ammonium dinitramide on mechanical sensitivity of propellants is less by replacing part of RDX. The amount of gas produced by ammonium dinitramide is greater than ammonium perchlorate (AP) in vacuum stability test, which reduce thermal stability of HTPB/ADN propellants. Under the pressure of 4-15 MPa, the pressure exponent of burning rate (n) of this propellants reach 0.70, which is higher than that of HTPB/AP propellants, while after adding iron-based catalyst, burning rate can be reduced to 0.60 or less. The combustion wave structure of this propellants is same as that of HTPB/AP propellants, but the slope of T-t curves increase more with pressure increasing.